The only EKG book you'll ever need - Thaler, Malcolm S. (Wolters Kluwer, 2019)
"The Only EKG Book You'll Ever Need presents the key information clinicians need to know about ECG use in their everyday practice. The founding principle of the book, to keep simple ideas simple and complicated ideas clear and concise, still holds true after 8 editions and has resulted in the book being widely adopted in to medical schools, career schools, and nursing schools"--Provided by publisher